2015
DOI: 10.1007/s13203-015-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZSM-5 zeolite from diatomite for fluid catalytic cracking (FCC) application

Abstract: In this study, ZSM-5 zeolite was successfully synthesized hydrothermally from cheap and easily accessible natural mineral diatomite in the presence of tetrapropyl ammonium bromide. The pore structure, acidic sites and surface features of as-synthesized ZSM-5 zeolite were well characterized by X-ray diffraction, scanning electron microscopy, pyridine-adsorbed Fourier transform infrared spectroscopy, and N 2 adsorption. The analysis results revealed that the as-synthesized ZSM-5 zeolite exhibited excellent hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Elemental analysis using AAS showed that Si-to-Al ratio of synthesized NaZSM-5 zeolite was 33.19. This makes ZSM-5 classified as high-silica zeolites (Si/Al ratio = ~10-100), which has played an important role as hydrocracking catalysis in petrochemistry due to its hydrophobic surfaces [17]. T − O (T = Si or Al) and the band at 650-500 cm −1 that can be attributed to the pentasil double-5-ring bending vibration [18].…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…Elemental analysis using AAS showed that Si-to-Al ratio of synthesized NaZSM-5 zeolite was 33.19. This makes ZSM-5 classified as high-silica zeolites (Si/Al ratio = ~10-100), which has played an important role as hydrocracking catalysis in petrochemistry due to its hydrophobic surfaces [17]. T − O (T = Si or Al) and the band at 650-500 cm −1 that can be attributed to the pentasil double-5-ring bending vibration [18].…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…Alternatively, clays such as diatomite, kaolin or rectorite can be used for ZSM-5 synthesis. [17][18][19] However, these starting materials contain impurities and do not allow precise crystallization control.…”
Section: Introductionmentioning
confidence: 99%
“…Although these chemicals provide good control over the crystallization and allow wide modifications of the product, they are comparatively expensive. Alternatively, clays such as diatomite, kaolin or rectorite can be used for ZSM‐5 synthesis [17–19] . However, these starting materials contain impurities and do not allow precise crystallization control.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional ZSM-5 zeolite synthesis method involves a gel formation obtained from different chemical reagents such as sodium silicate, aluminum sulfate, and tetrapropylammonium hydroxide (TPA-OH) [5], [6]. These chemical reagents are expensive, so it is convenient to use lower cost materials such as diatomaceous earth [7]- [11]. Due the importance of the Si/Al ratio in zeolite's properties, there are many studies in relation to modulating the Si/Al ratio of a nonmetallic mineral raw material such as kaolin and diatomaceous earth [7]- [9].…”
Section: Introductionmentioning
confidence: 99%